Agrarian questions and enduring peasants: a classic debate enters the age of globalisation. Disappearing Peasantries? rural labour in Africa, Asia and Latin America. Peasants, Populism and Postmodernism: the return of the agrarian myth - Borchgrevink, Axel
El artículo reseña dos libros: "Disappearing Pesasantries? Rural Labour in Africa, Asia and Latin America de Deborah Bryceson, Cristábal Kay y Jos Mooij" y "Peasants, Populism and Postmodernism: The Return of the Agrarian Myth" de Tom Brass